Best Interests or Autonomy? Navigating Parenting Disputes Over Children’s Treatment - Houston, Claire (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2025)
Family courts are struggling to resolve parenting disputes over children’s treatment. These cases ask judges to decide such sensitive matters as whether a young person will be vaccinated against their wishes, granted access to gender-affirming healthcare, or forced into therapy. Parenting disputes over children’s treatment implicate two distinct and potentially conflicting areas of law: family law and health law. Because family law and health law employ different legal standards and espouse different legal principles, the outcome in these cases may depend on which legal framework is applied. This article makes two contributions. First, it surveys recent family court decisions and suggests that courts are resolving parenting disputes over children’s treatment in one of three ways: (1) applying health law rather than family law; (2) drawing on health law principles in applying family law; and, most commonly, (3) applying family law rather than health law. Second, I look to larger debates around children’s welfare versus autonomy to make a case for how the apparent tension between family law and health law in these cases may be reconciled.